A Case Study on Obstacles to the Social Integration Process of Young People of Roma Origin - Szabó, Henriett (Ethnographica et Folkloristica Carpathica, 2023)
There are numerous obstacles to the advancement of Roma young people coming from disadvantaged social environments. Among these, the phenomenon that can be described by the expression köztes kitettség [verbatim: intermediate exposure] stands out. Social integration is an integration/assimilation practice complying with majority norms, which also means moving away from the values of one’s own local environment. According to the experience gained from research conducted on this topic, there are a lot of Roma young people who are trapped between two “societies” – their own sociocultural environment and the majority environment – and, consequently, find themselves in a special situation. The aim of this study is to shed light on the general context and the social significance of the phenomenon described above through recording field experiences and applying case analyses.